2001
DOI: 10.1111/j.1348-0421.2001.tb01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cell Structure of Flavobacterium psychrophilum with Length of Culture

Abstract: Flavobacterium psychrophilum, the pathogen of bacterial cold-water disease, causes serious problems in ayu Plecoglossus altivelis culture. This study investigated the effect of the culture period of F. psychrophilum and on the structure of its cells, From the SDS-PAGE of total proteins of ceUular components, much difference was found between the 36 hr culture and the 48 and 72 hr cultures. A SEM observation of the cells showed many fragments, especially on the cell surface of the 36 hr culture. These fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Changes in the cell morphology of Flavobacterium psychrophilum have been noted with increased culture time (Kondo et al 2001). Alterations in the cell morphology during starvation are also of interest.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Changes in the cell morphology of Flavobacterium psychrophilum have been noted with increased culture time (Kondo et al 2001). Alterations in the cell morphology during starvation are also of interest.…”
Section: Discussionmentioning
confidence: 93%
“…No viable bacteria could be detected by either culture counts or the live/dead kit 1 h after being placed in distilled water. Michel et al (1999) found Flavobacterium psychrophilum to be highly susceptible to osmotic changes.Changes in the cell morphology of Flavobacterium psychrophilum have been noted with increased culture time (Kondo et al 2001). Alterations in the cell morphology during starvation are also of interest.…”
mentioning
confidence: 93%
“…Our previous study (Kondo et al 2001b) showed that this bacterium possessed outer membrane components on the cell surface of the logarithmic phase culture. Rahman et al (2002) reported the effectiveness of the outer membrane fraction of BCWD.…”
mentioning
confidence: 91%
“…In the challenge test, bacteria in the logarithmic culture phase were used because this phase showed higher virulence than other phases (Kondo et al 2001b). The results showed that vaccination by either method gave significantly higher survival rates than the control in both challenge tests.…”
mentioning
confidence: 99%
“…produce OM vesicles in both intraphagosomal and extraphagosomal compartments (3,33,44,45). In the case of Flavobacterium, vesicles are made late in the growth phase (82). The mechanism of vesicle production is complex (95), and progress in this field will be updated in detail in a separate review (A. Kulp and M. J. Kuehn, unpublished data).…”
Section: Natural Om Vesiclesmentioning
confidence: 99%